Indonesian Presidential Election 2019 – Joko Widodo : Vulnerable Despite Strong Incumbency - Arifianto, Alexander Raymond (2019)
Incumbent Indonesian President Joko Widodo enters the 2019 presidential election with a strong advantage based on the support from political parties, politicians, and other notables. However, he remains vulnerable to attacks by his chief contender, Prabowo Subianto, on his economic achievements and Islamic credentials.